The Influence of Teaching Styles in Physical Education for a Healthy Lifestyle: Physical Activity and Physical Condition - Martín Sanz, Norma Teresa (Servicio de Publicaciones y Divulgación Científica, 2016)
Increased Moderate-Vigorous Physical Activity (MVPA) and reduced Sedentary Time (ST) are key factors for a healthy lifestyle during childhood and adolescence. Studies have suggested that schools may be effective resources to promote healthy habits (McKenzie, & Lounsbery, 2013). Therefore, in Physical Education (PE), is important to assess how teachers use strategies and provide students tools to engage in Physical Activity (PA) (Lonsdale, et al., 2013). Many factors may be involved in the successful PE class to promote healthy out-school behaviors, as Teaching Styles (TS), learning time, motivation and so on (Kulinna, & Cothran, 2003). Regarding TS, there is a lack of knowledge about influence of the TS in the promotion of daily PA. Purpose The first purpose was review the state of the art on pedagogical assessment tools to evaluate TS in PE. The second purpose was to observe the differences of total daily PA and Physical Condition (PC) variables between two groups of adolescents who were taught during two whole academic years using different TS and contents. Method Review: Several databases were used to identify literature that appeared to be relates to the use of TS in PE in elementary and secondary schools. We reviewed publications between 1st of January 1970 up to and including 31th of July 2015. Sample: 176 adolescents wore an Accelerometer (ACL) to record one week of total daily PA at the beginning and at end of course. Four groups of PE classes were taught with two different strategies: Reproduction of Knowledge (RK) and Production of Knowledge (PK), following the classical Spectrum (Mosston, & Ashworth, 2002) and comparing them with a control group that not used a precise TS, Mixed Knowledge (MK). After analyzing ACL data, 91 adolescents (49 boys and 42 girls) obtained valid records (attrition rate = 48,3%). Physical activity assessment: PA was recorded using ACLs (Actigraph GT3X). The inclusion criteria to considerer a complete day would be if it contained ≥ 10 hours for weekdays and ≥ 8 hours for weekend days (Yildirim, 2011). Only participants with ≥ 4 complete days, including one weekend day were included (Holman, Carson, & Jansson, 2011). Repeated measures analysis was carried out in order to compare differences between groups and time effect. Body composition: Height and weight were assessed. Anthropometry was used to estimate body composition (Alvero-Cruz, 2014). Fat Mass Percent (%FM) was calculated with Slaughter equations (Slaughter, 1988), and Fat Free Mass was calculated as [(FFM = Weight - (%FM · Weight))]. Skeletal Muscle Mass (SMM) (Poortmans, 2005; Lee, 2000). Physical Fitness: Strength on Right and Left Hands (RGS and LGS) was measured using a digital handgrip dynamometer (T.K.K.5401, Takei). Lower Limbs Strength (LLS) was measured with an isometric back-leg lift dynamometer (TKK-5002, Psymtec). Results and discussion Review: 526 potentially relevant publications and 373 references related to TS and PE. Physical activity, Body Compositon (BC) and Physical Fitness (PF) assessment: Significant differences were found between RK and MK for MVPA, Fat Mass (FM) and FFM (P < 0.05). Significant differences were found between RK and MK for Maximum Oxygen Uptake (VO2AMax), RGS, LGS, LLS and (P < 0.01). There were significant differences between 3rd and 1st content in ST, Light Physical Activity (LPA), Moderate Physical Activity (MPA), MVPA and Steps (P < 0.05). Conclusions 1. Five specific instruments in regard with TS using during PE lessons were found. 2. Our main finding related with PA was that PA patterns (minutes per day at specific intensities) were affected by change in TS. The PA volume and intensity levels varied based on different content and TS. Specifically, PK group raised significantly all PA daily patterns except sedentary time after one-academic year. Regarding to RK and MK, there were significant differences between these TS for VPA, MVPA and steps.
Keywords: Educación física; Methology; Tesis Doctoral; Physical Education; Teaching Style; Physical Condition; Physical Activity